Determinants of capital structure: An empirical analysis of listed non-financial firms in Malaysia / Nur Tiara Edzyan Mohd Kamal - Mohd Kamal, Nur Tiara Edzyan (Faculty of Business and Management, 2014)
Capital structure explained the mix of securities and financing sources used by corporations to finance real investment. Capital structure is one of the most important effective measures on the valuation and direction of economic enterprises in the capital markets. Capital structure can be influenced by internal and external factors. The internal factors that affect company capital structure can be controlled by managers and it is essential for managers to identify the determinants that can affect capital structure. Finance managers decisions on choosing the best capital structure are important because it will affect the company performance and shareholders wealth. This paper purpose is to examine the determinants of capital structure. This study is conducted to investigate the relationship between the factors of capital structure which are capital intensity (CI), tangibility (TANG), profitability (PFT), and firm size (FS) towards capital structure. The capital structure will be measured by debt ratio, long term debt and short term debt. This study is using secondary data and panel data analysis. The data is obtained from annual report of listed non-financial company in Malaysia. The annual report will be obtained from Bursa Malaysia for six selected listed non-financial firms in Malaysia. The data is collected for five years from 2008 to 2012.